Development of A Clinical Decision Support System for Calculus Risk Prediction - Marlindayanti, Marlindayanti; Dyah Utami, Wahyu Jati; Baizan , Annisa; Tsaliza Muntazi , Yasmin; Sepriani , Putri; ’Atun, Qori (Jurnal Kesehatan Gigi, 2025)
Oral health in Indonesia remains a significant problem, with 57.6% of the population experiencing problems but only 10.2% accessing treatment. Dental calculus is one of the main etiologies of periodontal disease. Therefore, healthcare professionals require a rapid and standardized screening tool to efficiently identify high-risk patients. This study aims to report the development process and trial results of the "Calrisk Dentistry" application, a clinical decision support system for detecting risk levels and identifying the main causative factors of calculus. This study used a cross-sectional design to conduct a trial of the system on 60 respondents. The trial was conducted on 60 patients, where the data collection process was facilitated by dental hygiene students. Data were collected using the "Calrisk Dentistry" application that analyzes 13 risk variables to generate a risk score. The application successfully classified respondents into four risk categories: Low (15%), Moderate (40%), High (31.7%), and Very High (13.3%). The risk factors with the highest impact identified by the system were inappropriate brushing time, one-sided chewing, and the presence of caries. The trial results indicate that the developed "Calrisk Dentistry" application is a functional and effective tool for calculus risk screening. This system has the potential to become a technological tool to increase patient awareness and facilitate early prevention.